2015
DOI: 10.3758/s13414-015-0963-9
|View full text |Cite
|
Sign up to set email alerts
|

Change detection on a hunch: Pre-attentive vision allows “sensing” of unique feature changes

Abstract: Studies on change detection and change blindness have investigated the nature of visual representations by testing the conditions under which observers are able to detect when an object in a complex scene changes from one moment to the next. Several authors have proposed that change detection can occur without identification of the changing object, but the perceptual processes underlying this phenomenon are currently unknown. We hypothesized that change detection without localization or identification occurs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…traffic, when suprathreshold stimuli can be easily missed (as shown by e.g. change blindness experiments 3 5 ). To summarize, while physical effectiveness can determine MSF in simple paradigms, internal and physical effectiveness might determine MSF in more complex paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…traffic, when suprathreshold stimuli can be easily missed (as shown by e.g. change blindness experiments 3 5 ). To summarize, while physical effectiveness can determine MSF in simple paradigms, internal and physical effectiveness might determine MSF in more complex paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the hypothesis of Rensink (2004) that seeing and sensing may be facilitated by separate mechanisms. Other studies have also found differences in ERP amplitudes when comparing trials with ‘full’ and ‘partial’ awareness (Fernandez-Duque et al, 2003; Kimura et al, 2008; Busch, 2013; Ball & Busch, 2015), but the definition of sense trials and ‘full’ awareness varies across studies (Mitroff et al, 2002), leading to divergent results.…”
Section: Introductionmentioning
confidence: 99%
“…Several other researchers have explored the possibility of an awareness condition that lies somewhere between the traditional see and blind dichotomy (Fernandez-Duque et al, 2003; Laloyaux et al, 2006; Thornton & Fernandez-Duque, 2001; Galpin et al, 2008; Busch et al, 2009; Ball & Busch, 2015; Kimura et al, 2008; Hollingworth et al, 2001). For example, Fernandez-Duque et al (2003) found that the location of a change could be identified above chance level even when participants did not report to see the change itself (but see Mitroff et al 2002 and Laloyaux et al 2006 for a discussion of these results).…”
Section: Introductionmentioning
confidence: 99%
“…Given this, the involvement of ensemble representations in the classical colour‐patch change‐detection task would predict that there is a considerable incidence of trials on which participants detect a change but are unable to localize it, whereas – excluding detection responses that simply happen to be correct as a result of random guessing – such trials should not occur when only individual‐item representations are involved. In fact, incidences of change detection or change classification without change localization are commonly observed in the change‐blindness literature (e.g., Agostinelli, Sherman, Fazio, & Hearst, ; Ball & Busch, ; Becker, Pashler, & Anstis, ; Busch, Dürschmid, & Herrmann, ; Hughes, Caplovitz, Loucks, Fendrich, & Hamed, ; Turatto & Bridgeman, ). For example, people can correctly classify whether the average emotion in a set of faces changed towards happier or angrier without being able to select a changed face (Haberman & Whitney, ).…”
Section: Introductionmentioning
confidence: 99%
“…Others refer to this phenomenon as detecting a change in the ‘gist’ of the scene (Haberman & Whitney, ). ‘Sensing’ a change and detecting a change in the ‘gist’ of a scene might just be detection of a change based on ensemble representations (Ball & Busch, ; Haberman & Whitney, ). However, change blindness studies differ in many respects from the typical colour‐change‐detection task: They typically involve a higher incidence of change trials (often up to 100%, as a result of which change‐detection accuracy cannot be measured) and shorter retention intervals (implying the involvement of iconic memory), as well as using more complex stimuli (thus providing more opportunities for using ensemble representations by grouping based on subcategories or other principles).…”
Section: Introductionmentioning
confidence: 99%